A review on decision making of risk mitigation for software management - Che Pa, Noraini; Anthony Jnr, Bokolo (Asian Research Publication Network, 2015)
Decision making (DM) is one of the main phases in risk mitigation for software management. DM is undeniably an essential phase in risk mitigation. Every decision has a different level of influence or impact in software management. In order to come up with the best choices, it's necessary to go through the decision making process and adopt an optimal decision making model or tool to aid risk decisions in risk mitigation. Many studies have been accompanied for viewing the issues from different aspects based on a systematic method which is called Systematic Literature Review (SLR). This review identifies the process, factors, frameworks, models of DM of risk mitigation in software management. The findings of this review indicate that DM is one of the complications in mitigating risk in software management.